Effect of planting density on diameter structure of black poplar clones S6-7 and M-1 - section Aigeiros [Duby] - Andrašev Siniša; Rončević Savo; Bobinac Martin T. (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2003)
The parameters of diameter structure of two black poplar clones in the section Aigeiros Duby (S6-7 and M-1) are presented depending on three different spacings: 3x3 m, 4.25x4.25 m and 6x6 m. Modeling of diameter structure was performed by Weibull’s function of probability distribution. We determined the effect of spacing (density) and clone both on the parameters and on the model diameter structure.